2012
DOI: 10.4067/s0718-19572012000300016
|View full text |Cite
|
Sign up to set email alerts
|

A new record of Azadinium spinosum (Dinoflagellata) from the tropical Mexican Pacific

Abstract: A new record of Azadinium spinosum (Dinoflagellata) from the tropical Mexican PacificAbstract.-The species Azadinium spinosum, a small thecate dinoflagellate, originally and recently described from the North Sea, was found for the first time in the tropical Pacific coast of Mexico. Description by light and scanning electron microscopy and abundance data are here provided. The morphology of the species agrees with the original description, including size, shape, presence of posterior spine and tabulation detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…In addition, the toxin profile of the A. poporum isolate from the Gulf of Mexico is identical with the profile of A. poporum from Argentinean shelf waters including the recently discovered AZA-2 phosphate (Tillmann et al, 2016), even though both isolates belong to different ribotypes: C (Argentinean isolate) and D (Gulf of Mexico isolate). In contrast, only AZA-1 was detected in mussels collected from Baja California, Mexico (García-Mendoza et al, 2014), consistent with the fact that A. spinosum is present in the Mexican Pacific (Herná ndez-Becerril et al, 2012). Interestingly, shellfish samples from Morocco (Taleb et al, 2006) and Portugal (Vale et al, 2008) show an AZA-profile with predominant AZA-2, followed by AZA-1, quite different from any shellfish sample from Ireland, Norway, Spain or France (Twiner et al, 2008).…”
Section: Toxin Profilesmentioning
confidence: 75%
See 1 more Smart Citation
“…In addition, the toxin profile of the A. poporum isolate from the Gulf of Mexico is identical with the profile of A. poporum from Argentinean shelf waters including the recently discovered AZA-2 phosphate (Tillmann et al, 2016), even though both isolates belong to different ribotypes: C (Argentinean isolate) and D (Gulf of Mexico isolate). In contrast, only AZA-1 was detected in mussels collected from Baja California, Mexico (García-Mendoza et al, 2014), consistent with the fact that A. spinosum is present in the Mexican Pacific (Herná ndez-Becerril et al, 2012). Interestingly, shellfish samples from Morocco (Taleb et al, 2006) and Portugal (Vale et al, 2008) show an AZA-profile with predominant AZA-2, followed by AZA-1, quite different from any shellfish sample from Ireland, Norway, Spain or France (Twiner et al, 2008).…”
Section: Toxin Profilesmentioning
confidence: 75%
“…Most Azadinium species were described from samples collected in European waters, but that does not mean that there is a restricted distribution of these small dinoflagellates. For example, Azadinium spinosum was also reported in the Mexican Pacific (Herná ndez-Becerril et al, 2012), and Azadinium poporum was found in Korea (Potvin et al, 2011), China , New Zealand (Smith et al, 2015) and Argentina (Tillmann et al, 2016). Azadinium diversity might be underestimated because their cells are rather small and molecular detection is not routinely carried out (Toebe et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Geographic distribution of this clade appears to be wide and may increase to new areas as the analysis of the nanoplanktonic size fraction, to which most of these species belong, could progress. To our knowledge, Azadinium has been recorded in the North Sea, in sub-Arctic and central areas of the North Atlantic, in some localities of Atlantic European coasts, the Mediterranean Sea, the austral Southwest Atlantic, and in the eastern (China, Korea and New Zealand) and western (Mexico) Pacific (Akselman & Negri 2012;Hernández-Becerril et al 2012;Nézan et al 2012;Potvin et al 2012;Gu et al 2013;Percopo et al 2013;Tillmann et al 2014c;Kaufmann et al 2015;Smith et al 2016), as well as in the Black Sea and the Indian Ocean (see Tillmann et al 2014c). The most common situation reported so far in various regions was the detection of AZAs in shellfish before (if at all) the record of their causative organisms in the planktonic realm.…”
Section: Introductionmentioning
confidence: 96%
“…Most species of Azadinium have been initially described from the North Sea but today, multiple records from various parts of the world are available (Akselman & Negri, 2012;Hernández-Becerril et al, 2012;Potvin et al, 2012;Gu et al, 2013;Luo et al, 2013;Percopo et al, 2013). However, knowledge about Amphidomataceae, and the presence of AZAs, in the (sub-)Arctic is still scarce (Poulin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%